Arctic campaign 2020 - YAK-AEROSIB - trace gas measurements - Paris, Jean-Daniel; Belan, Boris D.; Arshinov, Mikhail Yu.; Nédélec, Philippe; Belan, Sergei B.; Davydov, Denis; Fofonov, Alexander; Kozlov, Artem (Zenodo, 2023)
Trace gas measurements during the 2020 YAK-AEROSIB follow-upcampaign